SDG11-Based Sustainability Assessment of Urban Communities: A Case Study of Changsha - Qin Shuqian; Zhang Nan; Zhu Peijuan; Zhang Yong; Zhang Chen (Redai dili)
Given the real-world challenges in implementing the United Nations Sustainable Development Goals (SDGs), it is important to study and formulate a localized assessment indicator system for each SDGs to monitor the current status of sustainable development at different scales, identify problems, and develop countermeasures. Based on the "economy-society-environment" three-dimensional theoretical framework for sustainable development, this study deconstructs the connotation of SDG11 at the community level, and constructs an urban community sustainability assessment indicator system containing 7 goals and 13 indexes. In addition, by taking 602 sample communities in the built-up regions of Changsha as an example, this study utilizes multi-source big data to comprehensively assess community sustainability as well as the coupling coordination degree of the communities' economic-social-environmental systems. It is found that: (1) During the period 2010-2020, the degree of achievement of community SDG in Changsha falls in the "relative closeness" range, with a "core-periphery" spatial distribution from the high sections to the low ones. (2) Of the 7 goals, housing guarantee, disaster prevention and relief, and environmental governance are progressing well; public transportation and heritage protection are improving significantly; public space is rising slowly; however, planning management is less than ideal. (3) Based on the assessment results of the coupling coordination degree of the communities' economic-social-environmental systems, the sample communities are classified into three types: coordinated development, transitional development, and dysfunctional decline communities. Then, in addition to the zoning results of core, central urban, and suburban areas, a differentiated governance path is proposed. (4) The assessment indicator system has high validity and needs to be further enhanced with a larger number of empirical cases in the future. The research results enrich the theoretical system of community sustainability and technical means of assessment. The empirical part of the study takes the statutory communities in the built-up area of Changsha as the research object and carries out the assessment of community sustainability at three time points: 2010, 2015, and 2020. This help in grasping the temporal and spatial heterogeneity of community sustainability and its law of evolution at the city level and provide scientific support for carrying out refined urban planning and community governance. The data used in the indicator system mainly come from objective big data with temporal continuity, which is conducive for conducting longitudinal continuous tracking research and horizontal comparison research with other cities.